Adjunctive aids for the detection of oral premalignancy - D Charanya; L P Raghupathy; Amjad Fazeela Farzana; R Murugan; R Krishnaraj; G Kalarani (Wolters Kluwer Medknow Publications, 2016)
Early detection of cancer greatly decreases the morbidity and mortality rates and thereby increases the 5-year survival rates. In developing countries like India where the disease is highly prevalent focus is mainly on decreasing the mortality rates which can be easily achieved by detection at an asymptomatic stage. Visual examination has been the standard screening method for screening oral cancer through several decades, and it is well known that conventional visual examination is limited to subjective interpretation and cannot be easily achieved in certain anatomical sites. As a solution to all these adjunctive techniques have emerged, and it has been widely used. An effort is made through this paper to review the most commonly used adjunctive aids for the detection of premalignancy and cancer.